Electronic Voting 8th International Joint Conference, E-Vote-ID 2023, Luxembourg City, Luxembourg, October 3-6, 2023, Proceedings - Volkamer, Melanie; Duenas-Cid, David; Rønne, Peter; Ryan, Peter Y. A.; Budurushi, Jurlind; Kulyk, Oksana; Rodriguez Pérez, Adrià; Spycher-Krivonosova, Iuliia (Lecture Notes in Computer Science, 2023)
This open access book constitutes the proceedings of the 8th International Joint Conference on Electronic Voting held in Luxemburg in October 2023. The conference collected the most relevant debates on the development of Electronic Voting, from aspects relating to security and usability through to practical experiences and applications of voting systems, also including legal, social, or political aspects, amongst others. The 9 full papers presented were carefully reviewed and selected from 38 submissions. The selected papers cover a wide range of topics connected with electronic voting, including experiences and revisions of the actual uses of E-voting systems and corresponding processes in elections.